وباء الطاعون بالجزائر خلال العهد العثماني(1519-1830) - سمية عميرات (My University, 2025)
Summary: The study dealt with the plague epidemic that struck Algeria during the period of Ottoman rule, highlighting its major impact on Algerian society. The plague recurred in successive waves, causing significant human losses. The study examined the spread of the epidemic in the eastern and western regions of Algeria, focusing on its various types and the factors that facilitated its spread, such as the weakness of the healthcare system, trade movements between cities and rural areas, and constant contact with the outside world. The study also shed light on the profound effects of this epidemic on the social and economic structure of Ottoman Algeria. It revealed the response of the authorities, particularly through quarantine measures and attempts to import medical knowledge, while the population turned to traditional medicine. The study concluded that the plague epidemic was a key factor in the history of Ottoman Algeria. --------------------------- الملخصات: عالجت الدراسة وباء الطاعون الذي اجتاح الجزائر خلال فترة الحكم العثماني، مُظهِرة تأثيره الكبير على المجتمع الجزائري. فقد تكررت موجات الطاعون، مما أسفر عن خسائر بشرية فادحة. استعرضت الدراسة تفشي الوباء في بايلك الشرق والغرب، مُركِّزة على أنواعه المختلفة والأسباب التي ساعدت في انتشاره، مثل ضعف النظام الصحي وحركة التنقلات التجارية بين المدن والريف، فضلًا عن الاحتكاك المستمر مع الخارج. كما تم تسليط الضوء على الآثار العميقة لهذا الوباء على البنية الاجتماعية والاقتصادية في الجزائر العثمانية. وأظهرت الدراسة تجاوب السلطات من خلال إجراءات الحجر الصحي ومحاولات استجلاب المعرفة الطبية، في حين اعتمد السكان على الطب التقليدي. خلصت الدراسة إلى أن وباء الطاعون كان عنصرًا محوريًا في تاريخ الجزائر العثمانية. ----------------------- Résumé : L'étude a traité de l'épidémie de peste qui a frappé l'Algérie pendant la période de la domination ottomane, mettant en évidence son impact majeur sur la société algérienne. La peste s'est répétée sous forme de vagues successives, entraînant des pertes humaines considérables. L'étude a examiné la propagation de l'épidémie dans les régions de l'Est et de l'Ouest de l'Algérie, en se concentrant sur ses différents types et les causes ayant facilité sa propagation, telles que la faiblesse du système de santé, les mouvements commerciaux entre les villes et les campagnes, ainsi que le contact constant avec l'extérieur. L'étude a également mis en lumière les effets profonds de cette épidémie sur la structure sociale et économique de l'Algérie ottomane. Elle a révélé la réaction des autorités, notamment à travers des mesures de quarantaine et des tentatives d'importation de connaissances médicales, tandis que la population se tournait vers la médecine traditionnelle. L'étude a conclu que l'épidémie de peste a constitué un facteur clé dans l'histoire de l'Algérie ottomane.
Keywords: الوباء، الطاعون، الجزائر العثمانية، الحجر الصحي